An Autonomously Reciprocating Transmembrane Nanoactuator. Issue 4 (11th December 2015) - Watson, Matthew A.; Cockroft, Scott L.
Abstract: Biological molecular machines operate far from equilibrium by coupling chemical potential to repeated cycles of dissipative nanomechanical motion. This principle has been exploited in supramolecular systems that exhibit true machine behavior in solution and on surfaces. However, designed membrane‐spanning assemblies developed to date have been limited to simple switches or stochastic shuttles, and true machine behavior has remained elusive. Herein, we present a transmembrane nanoactuator that turns over chemical fuel to drive autonomous reciprocating (back‐and‐forth) nanomechanical motion. Ratcheted reciprocating motion of a DNA/PEG copolymer threaded through a single α‐hemolysin pore was induced by a combination of DNA strand displacement processes and enzyme‐catalyzed reactions. Ion‐current recordings revealed saw‐tooth patterns, indicating that the assemblies operated in autonomous, asymmetric cycles of conformational change at rates of up to one cycle per minute. Abstract : Machina trans membrana : A transmembrane nanoactuator turns over chemical fuel to drive autonomous nanomechanical motion. The ratcheted reciprocating motion of a DNA/PEG copolymer threaded through a single α‐hemolysin pore was induced by a combination of DNA strand displacement processes and enzyme‐catalyzed reactions.